Promotion And Lifestyle On The Decision To Use The E-Money Application Shopeepay - Putri Dewi, Naina (Al-Adzkiya Publisher, 2025)
The development of information technology affects promotion and lifestyle. One of them is the use of e-money applications used for transactions, consumers using e-money are usually influenced by several variables including promotions and lifestyles for that this study was conducted. Where the problems in this study consist of promotions that have not been maximized in providing promos and vouchers in using the Shopeepay application, the increase in the use of electronic money in transactions in 2022 on Shopeepay continues to increase from several other similar competitors, there are still some customers, especially the elderly who do not understand how to use Shopeepay and object to the administration fees given. The purpose of this study is to analyze the influence of promotions and lifestyle on the decision to use the Shopeepay e-money application in the Medan City community. This research method uses a quantitative associative approach. The population of this study is people who use Shopeepay in Medan City. In determining the sample of this study, there were 100 respondentsThe data collection technique used in this study was a questionnaire. The data analysis technique used in this study was multiple linear regression technique consisting of classical assumptions, partial (t) test, simultaneous (F), and coefficient of determination (R2). Data processing in this study used the SPSS application. The results of this study indicate that there is an influence of promotion on the decision to use e-money shopeepay with a calculated t value of 2.458> 1.984 t table with a sig value of 0.016 <0.05, there is an influence of lifestyle on the decision to use e-money shopeepay with a calculated t value of 6.358> 1.984 t table with a sig value of 0.000 <0.05. Simultaneously, the results of this study also show that there is an influence of promotion and lifestyle on the decision to use e-money shopeepay with a calculated f value of 30.154> 2.70 f table with a sig value of 0.000 <0.05. Research conclusion: there is a significant influence of promotion on the decision to use Shopeepay e-money, there is a significant influence of lifestyle on the decision to use Shopeepay e-money, simultaneously there is a significant influence of promotion and lifestyle on the decision to use the Shopeepay e-money application in the Medan City community.